Crystalline Polyether Nitrile

By introducing N and M repeat units of specific structures into the polymer and controlling their proportion and end-group structure, the problems of difficult to achieve high crystal quality, low melting point and high thermal stability in the prior art are solved, and the high performance and excellent processing performance of the polymer are achieved.

JP7666323B2Active Publication Date: 2025-04-22TORAY INDUSTRIES INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021530889
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-24
Filing Date
2021-05-24
Publication Date
2025-04-22
Estimated Expiration
2041-05-24

AI Technical Summary

Technical Problem

The prior art is difficult to achieve polymers with high crystalline quality, low melting point and high thermal stability at the same time, and there is a lack of effective methods for controlling and quantitative analysis of polymer end group structure.

Method used

Polymers with high crystalline quality, low melting point and high thermal stability are prepared by introducing N and M repeat units of specific structures into the polymer and controlling their proportions in the range of 0.90<[N/(N+M)]<1.00, combined with appropriate end group structure design and processing.

Benefits of technology

The high crystal quality, low melting point and high thermal stability of the polymer are achieved, and the processing performance and economicality of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666323000024
    Figure 0007666323000024
  • Figure 0007666323000025
    Figure 0007666323000025
  • Figure 0007666323000001
    Figure 0007666323000001
Patent Text Reader

Abstract

Provided is a crystalline polyether nitrile which has a melting point and a crystallization temperature during cooling, the difference therebetween being 40-100°C, and which has N repeating units represented by formula (I) and M repeating units represented by formula (II), the N and M being integers satisfying the relationship 0.90<[N / (N+M)]<1.00.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a crystalline copolymeric polyether nitrile. [Background technology]

[0002] Polyether nitrile is a type of crystalline super engineering plastic that has excellent heat resistance, chemical resistance, and flame retardancy, as well as excellent mechanical properties such as wear resistance and friction resistance (see, for example, Patent Document 1). Although polyethernitrile has the above-mentioned excellent properties, on the other hand, since it has a higher melting point than other thermoplastic resins, the processing temperature is high when processing polyethernitrile, such as injection molding, extrusion molding, etc. Therefore, there is a demand for polyethernitrile that has high crystallinity but a low melting point.

[0003] To address this issue, a method has been disclosed in which two types of dihydroxy components, which are constituent monomers, are copolymerized (see, for example, Patent Document 2 and Non-Patent Document 1). In addition, generally, active functional group terminals present in polymers are assumed to function as reaction points for polymer reactions or as points of interaction with additives, but they also cause a decrease in thermal stability, and therefore their blocking has been studied. In polyether nitriles, hydroxyl group terminals that may be present in the polymer are also considered to cause a decrease in thermal stability. In order to improve the thermal stability of polymers, a method of using a mono-substituted halogen compound as a reaction terminator (see, for example, Patent Document 3) and a method of using a monohydric phenol as a molecular weight regulator (see, for example, Patent Document 4) have been disclosed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 5-78576 [Patent Document 2] Special Publication No. 63-62526 [Patent Document 3] Japanese Patent Application Publication No. 63-270733 [Patent Document 4] Japanese Patent Application Publication No. 61-57619 [Non-patent literature]

[0005] [Non-Patent Document 1] High Performance Polymers,2019,31,310-320. Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the method shown in Patent Document 2, the crystallinity is completely lost and the product becomes amorphous, resulting in poor processability. Furthermore, there is no mention at all of how the copolymerization ratio affects the physical properties. In the method shown in Non-Patent Document 1, although the melting point is lowered, the crystallinity is also reduced, so that treatment at high temperature for several hours is necessary. However, none of the documents describes the mechanism or factors that enable control of high crystallinity and a low melting point.

[0007] In addition, while it is assumed that the hydroxyl group terminals that may be present in polyethernitrile can be used as reaction sites for polymer reactions or interaction sites with additives, their analysis is difficult, and no analysis has been reported on the hydroxyl group terminals that may be present in polyethernitrile or their quantification. In addition, since it is believed that the presence of a large amount of hydroxyl group terminals leads to a decrease in thermal stability, there have only been reports in which the polymer terminals are completely blocked by additives, as in Patent Document 3 and Patent Document 4, and no polyethernitriles have been reported in which the amount of hydroxyl group terminals in polyethernitrile is appropriately controlled and which have excellent thermal stability. Furthermore, in the methods shown in Patent Documents 3 and 4, it is necessary to use a third component other than the monomer in order to block the polymer ends, and there is room for improvement in terms of processability and economic efficiency.

[0008] In view of the problems with the conventional techniques, the present inventors have set an object to provide a crystalline polyether nitrile having high crystallinity, a low melting point and excellent thermal stability by controlling the difference between the melting point and the crystallization temperature during cooling within a specific range and by controlling and quantifying the terminal structure. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention has the following configuration. (1) A crystalline polyether nitrile, the difference between the melting point and the cooling crystallization temperature being 40°C or more and 100°C or less, having N repeating units represented by formula (I) and M repeating units represented by formula (II), N and M being integers satisfying the relationship 0.90<[N / (N+M)]<1.00. [ka] In formulas (I) and (II), Ar 1 and Ar 2 has one skeleton selected from the units represented by formula (a) to formula (f), provided that Ar 1 and Ar 2 are not identical. [ka] In the formulas (a) to (f), R is a linear organic group, a branched organic group, or a cyclic organic group having 1 to 6 carbon atoms, and may contain one or more oxygen atoms, nitrogen atoms, or sulfur atoms. R may be the same or different from each other. a indicates the number of substituents of R and is an integer of 0 to 4. X is a hydrogen atom or a methyl group.

[0010] (2) The crystalline polyethernitrile according to (1), which has N repeating units represented by formula (III) and M repeating units represented by formula (IV), wherein N and M are integers satisfying the relationship: 0.90<[N / (N+M)]<1.00. [ka] In formulas (III) and (IV), Ar 1 and Ar 2 has one skeleton selected from units represented by formula (g) to formula (l), provided that Ar 1 and Ar 2 are not identical. [ka] Here, X is a hydrogen atom or a methyl group.

[0011] (3) The crystalline polyethernitrile according to (1), which has N repeating units represented by formula (V) and M repeating units represented by formula (VI), wherein N and M are integers satisfying the relationship 0.90<[N / (N+M)]<1.00. [ka] In formulas (V) and (VI), Ar 1 and Ar 2 has one skeleton selected from units represented by formula (g) to formula (l), provided that Ar 1 and Ar 2 are not identical. [ka] Here, X is a hydrogen atom or a methyl group.

[0012] (4) Ar 1 The crystalline polyethernitrile according to any one of (1) to (3), wherein is a paraphenylene skeleton or a metaphenylene skeleton. (5) The crystalline polyethernitrile according to any one of (1) to (4), having a melting point of 280° C. or higher and 360° C. or lower. (6) The crystalline polyethernitrile according to any one of (1) to (5), which exhibits a weight loss rate of 5% or less when maintained at a temperature 30°C above the melting point for 30 minutes in a non-oxidizing atmosphere in thermogravimetric analysis (TG). Effect of the Invention

[0013] According to the present invention, it is possible to provide a crystalline polyether nitrile having high crystallinity, a low melting point and high thermal stability. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram showing the NMR spectrum of the crystalline polyether nitrile obtained in Example 1. [Diagram 2] FIG. 2 is an infrared spectrum chart of the crystalline polyethernitrile obtained in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the present invention will be described in detail with reference to embodiments. (1) Crystalline polyether nitrile The crystalline polyether nitrile of the present invention refers to a polymer having N repeating units represented by formula (I) and M repeating units represented by formula (II), where N and M are integers satisfying the relationship 0.90<[N / (N+M)]<1.00. [ka] In formula (I) and formula (II), Ar 1 and Ar 2 has one skeleton selected from the units represented by formula (a) to formula (f), provided that Ar 1 and Ar 2 are not identical. [ka] In the formulas (a) to (f), R is a linear organic group, a branched organic group, or a cyclic organic group having 1 to 6 carbon atoms, and may contain one or more oxygen atoms, nitrogen atoms, or sulfur atoms. R may be the same or different from each other. a indicates the number of substituents of R and is an integer of 0 to 4. X is a hydrogen atom or a methyl group.

[0016] The crystalline polyethernitrile according to the present invention has N repeating units represented by formula (I) and M repeating units represented by formula (II), where N and M are integers satisfying the relationship 0.90<[N / (N+M)]<1.00. The upper limit of [N / (N+M)] is not particularly limited as long as it is less than 1.00, but the closer it is to 1.00, the higher the melting point becomes, so it is preferably 0.99 or less, and more preferably 0.97 or less. The lower limit of [N / (N+M)] is not particularly limited as long as it is 0.90<, but if it is less than 0.90, the crystallinity decreases and the material becomes amorphous, which is not suitable. From the viewpoint of crystallinity, N and M are preferably integers satisfying the relationship 0.90<[N / (N+M)]≦0.99, more preferably integers satisfying the relationship 0.90<[N / (N+M)]≦0.97, and even more preferably integers satisfying the relationship 0.91≦[N / (N+M)]≦0.97. The upper limit of the sum of N and M is not particularly limited, but can be, for example, a range of 5 to 10,000, preferably a range of 5 to 5,000, more preferably a range of 5 to 1,000, and even more preferably a range of 5 to 500.

[0017] In the crystalline polyethernitrile of the present invention, preferred repeating units are represented by formula (III) and formula (IV). [ka] In the formula (III) and the formula (IV), Ar 1 and Ar 2 has one skeleton selected from units represented by formula (g) to formula (l), provided that Ar 1 and Ar 2 are not the same. The crystalline polyether nitrile has N repeating units represented by formula (III) and M repeating units represented by formula (IV), where N and M are integers satisfying the relationship 0.90<[N / (N+M)]<1.00. [ka]

[0018] Here, in formulas (g) to (l), X is a hydrogen atom or a methyl group. The crystalline polyethernitrile according to the present invention has N repeating units represented by formula (III) and M repeating units represented by formula (IV), where N and M represent integers satisfying the relationship 0.90<[N / (N+M)]<1.00. The upper limit of [N / (N+M)] is not particularly limited as long as it is less than 1.00, but the closer it is to 1.00, the higher the melting point becomes, so it is preferably 0.99 or less, and more preferably 0.97 or less. The lower limit of [N / (N+M)] is not particularly limited as long as it is 0.90<, but if it is less than 0.90, the crystallinity decreases and the product becomes amorphous, which is not suitable. From the viewpoint of crystallinity, N and M are preferably integers satisfying the relationship 0.90<[N / (N+M)]≦0.99, more preferably integers satisfying the relationship 0.90<[N / (N+M)]≦0.97, and even more preferably integers satisfying the relationship 0.91≦[N / (N+M)]≦0.97. The upper limit of the sum of N and M is not particularly limited, but can be, for example, a range of 5 to 10,000, preferably a range of 5 to 5,000, more preferably a range of 5 to 1,000, and even more preferably a range of 5 to 500.

[0019] In the crystalline polyethernitrile of the present invention, further preferred repeating units are represented by formulae (V) and (VI). [ka] In the formula (V) and the formula (VI), Ar 1 and Ar 2 has one skeleton selected from units represented by formula (g) to formula (l), provided that Ar 1 and Ar 2 are not the same. Among them, Ar 1 However, those having a skeleton represented by formula (g) or formula (h) are more preferred, and those represented by formula (g) are even more preferred. Ar 2 is more preferably represented by formula (g), formula (h), formula (i), formula (k) or formula (l), and Ar 1 When formula (g) is satisfied, Ar 2is preferably represented by formula (h), formula (i), formula (k) or formula (l); Ar 1 When formula (h) is given, Ar 2 is preferably the formula (g), the formula (i), the formula (k) or the formula (l). [ka]

[0020] In the formula, X is a hydrogen atom or a methyl group. The crystalline polyethernitrile according to the present invention has N repeating units represented by formula (V) and M repeating units represented by formula (VI), where N and M represent integers satisfying the relationship 0.90<[N / (N+M)]<1.00. The upper limit of [N / (N+M)] is not particularly limited as long as it is less than 1.00, but the closer it is to 1.00, the higher the melting point becomes, so it is preferably 0.99 or less, and more preferably 0.97 or less. The lower limit of [N / (N+M)] is not particularly limited as long as it is 0.90<, but if it is less than 0.90, the crystallinity decreases and the material becomes amorphous, which is not suitable. From the viewpoint of crystallinity, N and M are preferably integers satisfying the relationship 0.90<[N / (N+M)]≦0.99, more preferably integers satisfying the relationship 0.90<[N / (N+M)]≦0.97, and even more preferably integers satisfying the relationship 0.91≦[N / (N+M)]≦0.97. The upper limit of the sum of N and M is not particularly limited, but can be, for example, a range of 5 to 10,000, preferably a range of 5 to 5,000, more preferably a range of 5 to 1,000, and even more preferably a range of 5 to 500.

[0021] The crystalline polyethernitrile in the present invention is a crystalline polymer with excellent processability. Therefore, it is preferable that the crystallization temperature when cooled from a molten state, that is, the difference between the crystallization temperature and the melting point is small to a certain extent, but if it is too small, the moldability is deteriorated, so specifically, the difference between the melting point and the crystallization temperature needs to be 40 to 100°C. If it exceeds 100°C, the crystallinity is greatly reduced, which is not preferable. Also, if it is less than 40°C, the solidification speed of the molten polymer is fast and the processability is reduced, which is not preferable. The difference between the melting point and the crystallization temperature is more preferably 50 to 90°C.

[0022] In the present invention, the melting point of the crystalline polyether nitrile is from 280 to 360°C, preferably from 280 to 350°C, and more preferably from 280 to 340°C, from the viewpoint of processability. In the present invention, the terminal group of the crystalline polyether nitrile is a hydroxyl group, a metal salt of a hydroxyl group, a halogeno group, a linear organic group having 1 to 16 carbon atoms, a branched organic group, or a cyclic organic group. The structure of the terminal group of the crystalline polyethernitrile of the present invention affects the thermal stability. The thermal stability of the crystalline polyethernitrile of the present invention can be evaluated by thermogravimetric analysis (TG). In thermogravimetric analysis (TG), after holding at 50°C for 1 minute in a non-oxidizing atmosphere, the weight loss rate when heated from 50°C to melting point + 30°C at a temperature increase rate of 20°C / min and held at melting point + 30°C for 30 minutes is preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less. The weight loss rate is calculated based on the weight after holding at 50°C for 1 minute. The terminal structure of the crystalline polyethernitrile in the present invention can be quantified by nuclear magnetic resonance (NMR) analysis. The terminals of the polyethernitrile in the present invention are not particularly limited as long as they satisfy the above-mentioned thermal stability, but more preferably, the ratio of the sum of terminal groups other than hydroxyl groups and metal salts of hydroxyl groups, i.e., the sum of halogeno groups and linear organic groups, branched organic groups, and cyclic organic groups having 1 to 16 carbon atoms to all terminals, is 0.2 or more and 1.0 or less.

[0023] (2) Method for producing crystalline polyethernitrile The method for producing the polyethernitrile used in the present invention is not particularly limited as long as it can synthesize a polyethernitrile satisfying the requirement (1) above, and any method can be adopted. For example, the polyethernitrile can be produced by heating a mixture of an aromatic compound (M1) substituted with two hydroxyl groups, an aromatic compound (M2) other than the aromatic compound (M1) substituted with two hydroxyl groups, an aromatic compound (M3) having a benzonitrile skeleton substituted with two halogeno groups, and a base in an organic polar solvent.

[0024] The aromatic compound (M1) substituted with two hydroxyl groups, the aromatic compound (M2) substituted with two hydroxyl groups other than the aromatic compound (M1), the aromatic compound (M3) having a benzonitrile skeleton substituted with two halogeno groups, the base, the organic polar solvent, and the reaction conditions, which are used in a preferred embodiment of the present invention, are described below. In the method for producing a crystalline polyethernitrile of the present invention, the aromatic compound (M1) substituted with two hydroxyl groups and the aromatic compound (M2) other than the above (M1) substituted with two hydroxyl groups can be exemplified by compounds represented by the following general formulas (m) to (r). [ka] In the above formulas (m) to (r), R is a linear organic group, a branched organic group, or a cyclic organic group having 1 to 6 carbon atoms, and may contain one or more oxygen atoms, nitrogen atoms, or sulfur atoms. a indicates the number of substituents of R and is an integer of 0 to 4. When multiple Rs are present, the Rs may be the same or different from each other.

[0025] The compounds (M1) and (M2) substituted with two hydroxyl groups are specifically resorcinol, 5-methoxyresorcinol, 2-methylresorcinol, 5-methylresorcinol, 2,4-dihydroxybenzaldehyde, 4-ethylresorcinol, 3,5-dihydroxyacetophenone, 4-butylresorcinol, 2-acetylresorcinol, 4-hexylresorcinol, 4-acetylresorcinol, 3,5-dihydroxybenzoic acid, 4-benzoylresorcinol, 4,6-diacetylresorcinol, 2,6-dihydroxyphenylresorcinol, 4-phenyl-2 ... Benzoic acid, 2,4-dihydroxybenzoic acid, 4-propionylresorcinol, 3,5-dihydroxybenzamide, 3,5-dihydroxy-4-methylbenzoic acid, 2-nitroresorcinol, 2,6-dihydroxy-4-methylbenzoic acid, 2,4-dihydroxybenzamide, hydroquinone, 1,4-dihydroxynaphthalene, catechol, 4,4'-dihydroxybiphenyl, methylhydroquinone, methoxyhydroquinone, 2,6-dimethylhydroquinone, 2,3-dimethylhydroquinone, trimethylhydroquinone, tetramethylhydroquinone 2,5-di-tert-butylhydroquinone, 2,5-di-tert-amylhydroquinone, 2-acetylhydroquinone, 2,5-dihydroxybenzoic acid, phenylhydroquinone, 2,5-dihydroxyterephthalic acid, 1,4-dihydroxy-2-naphthoic acid, 3,6-dihydroxybenzonorbornane, 2,3-dihydroxynaphthalene, 1,2-dihydroxynaphthalene, 4-methylcatechol, 3-methoxycatechol, 3-methylcatechol, 3,4-dihydroxybenzaldehyde, 4-tert-butylcatechol, 2,3-Dihydroxybenzaldehyde, 3,4-dihydroxyacetophenone, 3,4-dihydroxybenzophenone, 3,5-di-tert-butylcatechol, 3,4-dihydroxybenzoic acid, 4-nitrocatechol, 2,3-dihydroxybenzoic acid, catechol-4-acetic acid, 4,4'-dihydroxy-3,3',5,5'-tetramethylbiphenyl, 3,3'-dihydroxybenzidine, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2,Examples include 2'-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, 1,1'-bis(4-hydroxyphenyl)methane, 4,4'-dihydroxybenzophenone, and 4,4'-dihydroxydiphenyl ether. From the viewpoint of economy, resorcinol, hydroquinone, catechol, 4,4'-dihydroxybiphenyl, 2,7-dihydroxynaphthalene, 2,2'-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, and 1,1'-bis(4-hydroxyphenyl)methane are preferred, and resorcinol, hydroquinone, catechol, 4,4'-dihydroxybiphenyl, 2,2'-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone are more preferred.

[0026] The crystalline polyethernitrile of the present invention may have a copolymer arrangement that is random or block, but is preferably random from the viewpoint of crystallinity, and the compound (M1) substituted with two hydroxyl groups and the compound (M2) are preferably mixed in advance and then reacted.

[0027] In the method for producing a crystalline polyethernitrile of the present invention, the compound (M3) having a benzonitrile skeleton substituted with two halogeno groups can be a compound represented by the following general formula (s). [ka] In formula (s), R is a linear organic group, a branched organic group, or a cyclic organic group having 1 to 6 carbon atoms, and may contain one or more oxygen atoms, nitrogen atoms, or sulfur atoms. a indicates the number of substituents of R and is an integer of 0 to 4. X 1 , X 2 are each independently a halogen atom and may be the same or different. When a plurality of R is present, R may be the same or different.

[0028] Specific examples of the compound (M3) having a benzonitrile skeleton substituted with two halogeno groups include 2,6-dichlorobenzonitrile, 2,6-difluorobenzonitrile, 2-chloro-6-fluorobenzonitrile, 2,5-dichlorobenzonitrile, 2-chloro-5-fluorobenzonitrile, 2,5-difluorobenzonitrile, 3,5-dichlorobenzonitrile, 3,5-difluorobenzonitrile, 2,3-dichlorobenzonitrile, 2,3-difluorobenzonitrile, 3-chloro-2-fluorobenzonitrile, 3,4-dichlorobenzonitrile, 3,4-difluorobenzonitrile, 4-chloro-3-fluorobenzonitrile, and 3-chloro-4-fluorobenzonitrile. From the viewpoint of economy, 2,6-dichlorobenzonitrile and 2,6-difluorobenzonitrile are preferred, and 2,6-dichlorobenzonitrile is more preferred.

[0029] In the method for producing the crystalline polyethernitrile of the present invention, the amounts of the compounds (M1), (M2), and (M3) used are not particularly limited as long as the sum of the compounds (M1) and (M2) is within a range of 0.90 to 1.10 mol per 1.00 mol of the compound (M3). From the viewpoint of the physical properties of the polymer, the amount is preferably within a range of 0.95 to 1.05 mol, and more preferably within a range of 0.95 to 1.00 mol. The amounts of the compounds (M1) and (M2) used are not particularly limited as long as they are within the range satisfying the relationship: 0.90<[amount (mol) of (M1) used / total amount (mol) of (M1) and (M2) used]<1.00. From the viewpoint of the polymer properties, however, it is more preferable that they are 0.91≦[amount (mol) of (M1) used / total amount (mol) of (M1) and (M2) used]<1.00, and more preferably 0.95≦[amount (mol) of (M1) used / total amount (mol) of (M1) and (M2) used]<1.00.

[0030] In the method for producing the crystalline polyethernitrile of the present invention, the base may be an organic base or an inorganic base. Specifically, organic bases such as 1,8-diazabicyclo[5.4.0]-7-undecene, 1,5-diazabicyclo[4.3.0]-5-nonene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, etc.; alkali metal carbonates such as lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, cesium carbonate, etc.; alkaline earth metal carbonates such as calcium carbonate, strontium carbonate, barium carbonate, etc.; alkali metal bicarbonates such as lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, cesium hydrogen carbonate, etc.; carbon dioxide. Examples of the base include bicarbonates of alkaline earth metals such as calcium hydrogen carbonate, strontium hydrogen carbonate, and barium hydrogen carbonate, hydroxides of alkaline metals such as lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide, and hydroxides of alkaline earth metals such as calcium hydroxide, strontium hydroxide, and barium hydroxide. Among them, from the viewpoint of ease of handling and reactivity, carbonates such as sodium carbonate and potassium carbonate, and bicarbonates such as sodium hydrogen carbonate and potassium hydrogen carbonate are preferred, sodium carbonate and potassium carbonate are more preferred, and sodium carbonate is even more preferred. These may be used alone or in combination of two or more kinds. In addition, these bases are preferably used in the form of anhydride, but can also be used as hydrates or aqueous mixtures. The aqueous mixture here refers to an aqueous solution, a mixture of an aqueous solution and a solid component, or a mixture of water and a solid component.

[0031] In the method for producing the crystalline polyethernitrile of the present invention, the amount of the base depends on the sum of the amounts of the aromatic compound (M1) and the aromatic compound (M2). The molar ratio of the base to the total number of moles of hydroxyl groups of the compounds (M1) and (M2) is at least 1, and from the viewpoint of reactivity, it is preferably 1.2 or more. Since the base in the present invention can be produced without problems even if used in excess, there is no particular upper limit, but the practical upper limit is 100 to the total number of moles of hydroxyl groups of (M1) and (M2). Preferably, the molar ratio of the base to the total number of moles of hydroxyl groups of (M1) and (M2) is 1.2 to 10. In the preferred method for producing the crystalline polyethernitrile of the present invention, the organic polar solvent to be used is not particularly limited as long as it does not inhibit the reaction. Specific examples of such organic polar solvents include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone (NMP), N-methylcaprolactam, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), 1,3-dimethyl-2-imidazolidinone (DMI), hexamethylphosphoramide, and tetramethylurea, sulfoxide-sulfone solvents such as dimethyl sulfoxide (DMSO), dimethyl sulfone, diphenyl sulfone, and sulfolane, nitrile solvents such as benzonitrile, diaryl ethers such as diphenyl ether, ketones such as benzophenone and acetophenone, and mixtures thereof. All of these are preferably used because of their high reaction stability, and among them, NMP, DMSO, and sulfolane are preferred, and NMP is particularly preferred. These organic polar solvents have excellent stability in the high temperature range, and are also preferred from the viewpoint of availability.

[0032] The amount of the organic polar solvent is preferably 0.50 liters or more per 1.0 mole of the total benzene ring components contained in the mixture, more preferably 1.00 liters or more, and even more preferably 2.0 liters or more. There is no particular upper limit on the amount of the organic polar solvent in the mixture, but it is preferably 100 liters or less, more preferably 50 liters or less, per 1.0 mole of the total benzene ring components in the mixture. If the amount of the organic polar solvent used is increased, the solubility of the monomer and the oligomer in the production process is improved, and it is possible to efficiently introduce reactive terminal groups. However, if the amount of the organic polar solvent used is too large, the amount of crystalline polyethernitrile produced per unit volume of the reaction vessel tends to decrease, and the time required for the reaction tends to increase. Therefore, from the viewpoint of productivity, it is preferable to use the organic polar solvent in the above-mentioned range. The amount of the organic polar solvent here is based on the volume of the solvent at normal temperature and normal pressure, and the amount of the organic polar solvent used in the mixture is the amount of the organic polar solvent introduced into the reaction system minus the amount of the organic polar solvent removed from the reaction system by a dehydration operation or the like. The benzene ring components in the mixture herein refer to benzene ring components contained in raw materials that can become constituent components of repeating units in the crystalline polyethernitrile through a reaction, and the "number of moles" of the benzene ring components in these raw materials refers to the "number of benzene rings constituting the compound." If necessary, a molecular weight regulator can be added. As the molecular weight regulator, a compound represented by the following formula (t) can be used. [ka] In formula (t), R is any one of a linear organic group, a branched organic group, and a cyclic organic group having 1 to 10 carbon atoms, and may contain one or more oxygen atoms, nitrogen atoms, and sulfur atoms. R may be the same or different from each other. a indicates the number of substituents of R and is an integer of 0 to 4. Specific examples include phenol, 4-phenylphenol, 4-tert-butylphenol, 4-cumylphenol, 4-phenoxyphenol, 4-ethylphenol, 4-methoxyphenol, and 4-tert-octylphenol.

[0033] In the method for producing the crystalline polyethernitrile of the present invention, water is by-produced as the reaction proceeds. In order to remove the by-produced water, an organic compound that forms an azeotrope with water can be added as necessary. Such an organic compound is not particularly limited as long as it forms an azeotrope with water, but a non-polar organic solvent having a boiling point lower than that of the reaction solvent is preferable, and specifically, toluene can be mentioned. The amount of the organic compound is not particularly limited as long as it does not inhibit the reaction, but is preferably in the range of 0 to 50%, more preferably in the range of 0 to 20%, and even more preferably in the range of 0 to 10%, by volume, relative to the amount of the organic polar solvent.

[0034] The method for producing the crystalline polyethernitrile of the present invention is carried out under heating under a nitrogen atmosphere or under reduced pressure. The reaction temperature can be varied over a wide range, but is carried out at a temperature of at least 80°C, preferably at least 150°C, and at most 400°C, and from the viewpoint of manufacturability, is preferably carried out at a temperature of at most 350°C. In consideration of the sublimability and reactivity of the compound used, it is preferable to carry out the reaction while gradually increasing the temperature in the range of 150°C to 350°C, more preferably in the range of 150°C to 200°C. Furthermore, it is more preferable to carry out the reaction while stirring in order to improve the reactivity.

[0035] The reaction time in the method for producing the crystalline polyethernitrile of the present invention can vary widely depending to some extent on the reaction temperature, the properties of the reagents used, and the presence of a solvent, but is 0.1 to 100 hours, preferably 0.5 to 50 hours from the viewpoint of productivity. The reaction vessel in the process for producing a crystalline polyethernitrile of the present invention is not particularly limited as long as it can withstand the above-mentioned reaction temperature, and a glass vessel or a stainless steel vessel can be used.

[0036] In the method for producing the crystalline polyethernitrile of the present invention, the pressure applied to the reaction may be sufficient to maintain the reactants in a liquid phase in the reaction medium, and may be in the range of 1 atm to 10 atm, and preferably, from the viewpoint of productivity, is 1 atm to 2 atm. In the method for producing the crystalline polyethernitrile of the present invention, the produced crystalline polyethernitrile can be obtained by separating and recovering it from the reaction mixture obtained by the above-mentioned production method. The reaction mixture obtained by the above-mentioned production method contains at least crystalline polyethernitrile, and may contain unreacted raw materials, by-product salts, unreacted bases, etc. as other components. There is no particular limitation on the method for recovering the crystalline polyethernitrile from such a reaction mixture, and examples thereof include a method of recovering the crystalline polyethernitrile by contacting it with a solvent that dissolves the by-product salt under heating as necessary, and a method of removing the by-product salt and the unreacted organic base under reduced pressure.

[0037] In the method of recovering the by-product salt by contacting it with a solvent capable of dissolving the by-product salt, optionally under heating, the solvent used is generally a solvent having a relatively high polarity. Preferred solvents vary depending on the type of base and by-product salt used, but examples include water, alcohols such as methanol, ethanol, propanol, isopropanol, butanol, and hexanol, ketones such as acetone and methyl ethyl ketone, acetates such as ethyl acetate and butyl acetate, nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone (NMP), N-methylcaprolactam, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), 1,3-dimethyl-2-imidazolidinone (DMI), hexamethylphosphoramide, and tetramethylurea, sulfoxide / sulfone solvents such as dimethyl sulfoxide (DMSO), dimethyl sulfone, diphenyl sulfone, and sulfolane, and acids such as acetic acid, hydrochloric acid, sulfuric acid, and nitric acid. From the viewpoints of availability and economy, water, methanol, acetone, acetic acid, hydrochloric acid, sulfuric acid, and NMP are preferred, and water, acetic acid, hydrochloric acid, and NMP are more preferred. In the method of removing by-product salts and unreacted organic base under reduced pressure, the reaction may be carried out at a pressure ranging from 0.001 to 1 atm, if necessary, under heating, after completion of the reaction.

[0038] The structure of the crystalline polyether nitrile in the present invention can be confirmed by infrared spectroscopy or nuclear magnetic resonance spectroscopy. The crystalline polyethernitrile according to the present invention is excellent in heat resistance, chemical resistance, flame retardancy, electrical properties and mechanical properties, and can be injection molded, injection compression molded, blow molded and extrusion molded. In this case, the crystalline polyethernitrile may be used alone, or, if desired, inorganic fillers such as glass fiber, carbon fiber, titanium oxide and calcium carbonate, antioxidants, heat stabilizers, ultraviolet absorbers, colorants and the like may be added, and resins other than the crystalline polyethernitrile according to the present invention may also be blended.

[0039] The crystalline polyethernitrile of the present invention may have a hydroxyl group at the end. In that case, it is expected that the polyethernitrile will have excellent adhesive properties with other resins or materials, and that the thermal properties can be controlled by the interaction between the additive and the hydroxyl group end. Applications include electrical and electronic components, home and office electrical appliance parts, optical equipment and precision machinery parts, plumbing parts, automotive and vehicle parts, and other industrial applications. EXAMPLES

[0040] The present invention will be described in detail below with reference to examples, which are illustrative and not limiting. <Structure confirmation> The structure of the crystalline polyether nitrile of the present invention was confirmed by infrared spectroscopy (IR) or nuclear magnetic resonance spectroscopy (NMR). IR was measured by the KBr pellet method using an IRP Research 21 manufactured by Shimadzu Corporation. NMR was measured by 1H-NMR in deuterated DMSO or in a mixed solvent of pentafluorophenol / deuterated chloroform = 5 / 3 (volume ratio) using a JNM-ECZ-500R manufactured by JEOL Ltd., and the ratio of [N / (N+M)] and the ratio of terminals other than hydroxyl groups and metal salts of hydroxyl groups to all terminals were calculated from the ratio of integral values ​​of the obtained spectrum.

[0041] <Molecular weight measurement> The molecular weight of the crystalline polyethernitrile of the present invention was determined by gel permeation chromatography (GPC), which is a type of size exclusion chromatography (SEC), or by NMR. GPC was measured at 250°C in 1-chloronaphthalene using SSC-7110 manufactured by Senshu Scientific Co., Ltd., and calculated in terms of polystyrene. NMR was calculated from the ratio of the integral value of the peak derived from the terminal group to the integral value of the peak derived from the main chain.

[0042] <Melting point, glass transition temperature, and crystallization temperature measurement> The melting point (Tm), glass transition temperature (Tg), and cooling crystallization temperature (Tc) of the crystalline polyether nitrile of the present invention were measured by differential scanning calorimetry (DSC). The DSC measurement was performed using a Q20 made by TA Instruments. The temperature was raised from 50°C to 400°C at 20°C / min, and the sample was held at 400°C for 1 minute, then cooled from 400°C to 50°C at 20°C / min, and again heated from 50°C to 400°C at 20°C / min, held at 400°C for 1 minute, and cooled from 400°C to 100°C at 20°C / min. The melting point was calculated from the results obtained during the second heating, and the cooling crystallization temperature was calculated from the results obtained during the second cooling. From the obtained melting point and cooling crystallization temperature, the "melting point - cooling crystallization temperature" was calculated.

[0043] <Thermogravimetric analysis (TG)> Equipment: PerkinElmer TGA7 Measurement atmosphere: Nitrogen flow Heating program: (a) Program temperature 50℃ for 1 minute (b) From the program temperature of 50°C, heat at a rate of 20°C / min to the melting point + 30°C if the compound is crystalline, or to the glass transition point + 100°C if the compound is amorphous. (c) If the compound is crystalline, keep it at the melting point + 30℃ for 30 minutes. If the compound is amorphous, keep it at the glass transition point + 100℃ for 30 minutes. Weight loss rate: The weight after 1 minute at 50°C was used as the base weight. If the compound was crystalline, the weight loss rate was calculated from the weight after 30 minutes at the melting point + 30°C. If the compound was amorphous, the weight loss rate was calculated from the weight after 30 minutes at the glass transition point + 100°C.

[0044] <Raw materials used in the examples> Dihydroxyl-substituted aromatic compounds (M1) and (M2) (M-1) Hydroquinone (FUJIFILM Wako Pure Chemical Corporation) (M-2) Resorcinol (FUJIFILM Wako Pure Chemical Corporation) (M-3) 4,4'-dihydroxybiphenyl (Tokyo Chemical Industry Co., Ltd.) (M-4) 2,2-bis(4-hydroxyphenyl)propane (Tokyo Chemical Industry Co., Ltd.) (M-5) 1,6-dihydroxynaphthalene (Tokyo Chemical Industry Co., Ltd.) (M-6) Catechol (Tokyo Chemical Industry Co., Ltd.) Compounds with a benzonitrile skeleton substituted with two halogeno groups (M3) (M3-1) 2,6-Dichlorobenzonitrile (Tokyo Chemical Industry Co., Ltd.) (M3-2) 2,6-Difluorobenzonitrile (Tokyo Chemical Industry Co., Ltd.) base (B-1) Sodium carbonate (Kanto Chemical Co., Ltd.) (B-2) Potassium carbonate (Kanto Chemical Co., Ltd.) Organic Polar Solvents (S-1) NMP (FUJIFILM Wako Pure Chemical Corporation) Molecular Weight Regulator (A-1) 4-tert-butylphenol (Kanto Chemical Co., Ltd.)

[0045] [Example 1] In a 300mL separable flask equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark tube, 8.37g (76.0mmol) of hydroquinone as an aromatic compound (M1), 0.44g (4.0mmol) of resorcinol as an aromatic compound (M2), 13.93g (81.0mmol) of 2,6-dichlorobenzonitrile as a compound (M3) having a benzonitrile skeleton, and 9.33g (88.0mmol) of sodium carbonate as a base were charged, and 80mL of NMP and 3mL of toluene were added under a nitrogen atmosphere, and the mixture was reacted at 160°C for 0.5 hours and then at 200°C for 5 hours. After the reaction was completed, the mixture was cooled to room temperature, and 80mL of NMP and 600mL of water were added. The obtained solid was further washed with 600mL of warm water (80°C) to obtain 14.0g of a white solid. As a result of NMR measurement, a peak derived from the chloro group terminal was observed at 6.97-6.99 ppm, a peak derived from the hydroxyl group terminal at 7.11-7.13 ppm, a peak derived from resorcinol (one proton at position 2) at 7.16 ppm, a peak derived from hydroquinone (four protons at positions 2, 3, 5, and 6) at 7.41 ppm, and a peak derived from the benzonitrile skeleton of the main chain (one proton at position 3) at 7.59-7.62 pm. From the ratio of the respective integral values, [N / (N+M)], molecular weight (Mn), and the ratio of halogeno groups to both ends were calculated. The melting point (Tm) was 341°C, the glass transition temperature (Tg) was 176°C, the cooling crystallization temperature (Tc) was 265°C, and the "melting point-cooling crystallization temperature" was 76°C. The weight loss rate when kept at the melting point +30°C for 30 minutes was 0.2%.

[0046] [Example 2] The same procedure as in Example 1 was carried out except that the amount of hydroquinone used was 8.02 g (72.8 mmol), the amount of resorcinol used was 0.79 g (7.2 mmol), and the amount of sodium carbonate used was 8.48 g (80.0 mmol), to obtain 14.1 g of a white solid. IR measurement was carried out on the obtained solid, and the result was -1 , 1580cm -1 , 1460cm -1 , 1240cm -1 , 1020cm -1 , 850cm-1 , 780cm -1 A peak indicating a crystalline polyether nitrile skeleton was observed.

[0047] [Example 3] The same procedure as in Example 1 was carried out except that the amount of hydroquinone used was 8.79 g (79.8 mmol) and 0.04 g (0.2 mmol) of 4,4'-dihydroxybiphenyl was used as the aromatic compound (M2), to obtain 14.8 g of a white solid.

[0048] [Example 4] The same procedure as in Example 1 was carried out except that 0.91 g (4.0 mmol) of 2,2-bis(4-hydroxyphenyl)propane was used as the aromatic compound (M2), thereby obtaining 15.0 g of a white solid.

[0049] [Example 5] In a 300mL separable flask equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark tube, 8.02g (72.8mmol) of hydroquinone as an aromatic compound (M1), 1.34g (7.2mmol) of 4,4'-dihydroxybiphenyl as an aromatic compound (M2), 0.12g (0.8mmol) of 4-tert-butylphenol as a molecular weight regulator, 13.93g (81.0mmol) of 2,6-dichlorobenzonitrile as a compound (M3) having a benzonitrile skeleton, and 9.33g (88.0mmol) of sodium carbonate as a base were charged, and 80mL of NMP and 3mL of toluene were added under a nitrogen atmosphere, and the mixture was reacted at 160°C for 0.5 hours and then at 200°C for 5 hours. After the reaction was completed, the mixture was cooled to room temperature, and 80mL of NMP and 600mL of water were added. The obtained solid was further washed with 600 mL of warm water (80° C.) to obtain 14.0 g of a white solid.

[0050] [Example 6] Except for using 8.37 g (76.0 mmol) of resorcinol as the aromatic compound (M1) and 0.44 g (4.0 mmol) of hydroquinone as the aromatic compound (M2), the same procedure as in Example 1 was carried out to obtain 14.0 g of a white solid. The molecular weights (Mn, Mw) were calculated by GPC measurement.

[0051] [Example 7] The same procedure as in Example 1 was carried out except that 0.44 g (4.0 mmol) of catechol was used as the aromatic compound (M2), thereby obtaining 13.9 g of a white solid.

[0052] [Example 8] Except for using 14.86 g (79.8 mmol) of 4,4'-dihydroxybiphenyl as the aromatic compound (M1) and changing the amount of resorcinol used to 0.02 g (0.2 mmol), the same operation as in Example 1 was carried out to obtain 14.8 g of a white solid. The molecular weights (Mn, Mw) were calculated by GPC measurement. [Example 9] The same procedure as in Example 5 was carried out except that the amount of hydroquinone used was 8.02 g (72.8 mmol), 0.79 g (7.2 mmol) of resorcinol was used as the aromatic compound (M2), and 0.24 g (1.6 mmol) of 4-tert-butylphenol was used, to obtain 13.8 g of a white solid.

[0053] [Comparative Example 1] Except for changing the amount of hydroquinone used to 6.61 g (60.0 mmol), the amount of resorcinol used to 2.20 g (20.0 mmol), and the amount of 2,6-dichlorobenzonitrile used to 14.10 g (82.0 mmol), the same procedure as in Example 1 was carried out to obtain 14.1 g of a white solid. The molecular weights (Mn, Mw) were calculated by GPC measurement.

[0054] [Comparative Example 2] A white solid weighing 14.2 g was obtained by carrying out the same procedure as in Example 1, except that 6.17 g (56.0 mmol) of resorcinol was used as the aromatic compound (M1), 4.47 g (24.0 mmol) of 4,4'-dihydroxybiphenyl was used as the aromatic compound (M2), and 12.11 g (70.4 mmol) of 2,6-dichlorobenzonitrile was used. The molecular weights (Mn, Mw) were calculated by GPC measurement.

[0055] [Comparative Example 3] A 300mL separable flask equipped with a stirrer, nitrogen inlet tube, and Dean-Stark tube was charged with 8.81g (80mmol) of hydroquinone, 14.10g (82mmol) of 2,6-dichlorobenzonitrile, and 9.75g (92mmol) of sodium carbonate, and under a nitrogen atmosphere, 80mL of NMP and 3mL of toluene were added, and the mixture was reacted at 160°C for 0.5 hours and then at 200°C for 5 hours. After the reaction was completed, the mixture was cooled to room temperature, and 80mL of NMP and 600mL of water were added. The obtained solid was further washed with 600mL of warm water (80°C) to obtain 14.0g of a white solid. [Comparative Example 4] Except for changing the amount of hydroquinone used to 6.17 g (56.0 mmol), the amount of resorcinol used to 2.64 g (24.0 mmol), and the amount of 2,6-dichlorobenzonitrile used to 14.10 g (82.0 mmol), the same procedure as in Example 1 was carried out to obtain 14.0 g of a white solid. The molecular weights (Mn, Mw) were calculated by GPC measurement. [Comparative Example 5] Except for using 7.45g (40.0mmol) of 4,4'-dihydroxybiphenyl as the aromatic compound (M1), 6.41g (40.0mmol) of 1,6-dihydroxynaphthalene as the aromatic compound (M2), 11.27g (81.0mmol) of 2,6-difluorobenzonitrile as the compound (M3) having a benzonitrile skeleton, and 12.16g (88.0mmol) of potassium carbonate as the base, the same operation as in Example 1 was performed to obtain 18.2g of a white solid. The molecular weights (Mn, Mw) were calculated by GPC measurement. [Comparative Example 6] The same procedure as in Example 1 was carried out except that 7.93 g (72.0 mmol) of hydroquinone was used and 1.83 g (8.0 mmol) of 2,2-bis(4-hydroxyphenyl)propane was used as the aromatic compound (M2), to obtain 15.0 g of a white solid. [Comparative Example 7] The same procedure as in Example 1 was carried out except that 7.93 g (72.0 mmol) of hydroquinone was used and 0.88 g (8.0 mmol) of catechol was used as the aromatic compound (M2), thereby obtaining 14.0 g of a white solid.

[0056] [Table 1]

[0057] [Table 2]

[0058] From the results of Examples 1 to 9, by setting the amount of aromatic compounds (M1) and (M2) used within a range satisfying the relationship of 0.90<[amount of (M1) used (mol) / total amount of (M1) and (M2) used (mol)]<1.00, [N / (N+M)] was in the range of 0.90<[N / (N+M)]<1.00, the difference between the melting point and the crystallization temperature by cooling was 40 to 100°C, the melting point was 280 to 360°C, and by controlling the terminal structure, a crystalline polyethernitrile with excellent thermal stability was obtained. On the other hand, from the results of Comparative Examples 1, 2, 4, 5, 6, and 7, when the amount of aromatic compounds (M1) and (M2) used was outside the above range, the crystallinity was greatly reduced. Furthermore, from the results of Comparative Example 2, when the amount of halogeno group terminals was reduced, the thermal stability was reduced. Furthermore, from the results of Comparative Example 3, the polymer from a single monomer had a high melting point of 373°C.

Claims

1. A crystalline polyether nitrile having a difference between its melting point and its crystallization temperature of 40° C. or more and 100° C. or less, and having N repeating units represented by formula (I) and M repeating units represented by formula (II), wherein N and M are integers satisfying the relationship 0.90<[N / (N+M)]<1.

00. 【Chemistry 1】 In formulas (I) and (II), Ar 1 has one skeleton selected from units represented by formula (a) and formula (b), and Ar 2 has one skeleton selected from units represented by formula (a) to formula (f). 1 and Ar 2 are not the same.) 【Chemistry 2】 (In formulas (a) to (f), R is any one of a linear organic group, a branched organic group, and a cyclic organic group having 1 to 6 carbon atoms, and may contain one or more oxygen atoms, nitrogen atoms, and sulfur atoms. R may be the same or different from each other. a represents the number of substituents on R, where a is 0 in Ar 1 and a is an integer of 0 to 4 in Ar 2 . X is a hydrogen atom or a methyl group.)

2. The crystalline polyether nitrile according to claim 1, which has N repeating units represented by formula (III) and M repeating units represented by formula (IV), and N and M are integers satisfying the relationship 0.90<[N / (N+M)]<1.

00. 【Chemistry 3】 In formulas (III) and (IV), Ar 1 has one skeleton selected from units represented by formula (g) and formula (h), and Ar 2 has one skeleton selected from units represented by formula (g) to formula (l). 1 and Ar 2 are not the same.) 【Chemistry 4】 (wherein X is a hydrogen atom or a methyl group).

3. The crystalline polyether nitrile according to claim 1, which has N repeating units represented by formula (V) and M repeating units represented by formula (VI), and N and M are integers satisfying the relationship 0.90<[N / (N+M)]<1.

00. 【Chemistry 5】 In the formulas (V) and (VI), Ar 1 has one skeleton selected from units represented by formula (g) and formula (h), and Ar 2 has one skeleton selected from units represented by formula (g) to formula (l). 1 and Ar 2 are not the same.) 【Chemistry 6】 (wherein X is a hydrogen atom or a methyl group).

4. The crystalline polyether nitrile according to any one of claims 1 to 3, having a melting point of 280°C or higher and 360°C or lower.

5. The crystalline polyethernitrile according to any one of claims 1 to 4, which exhibits a weight loss rate of 5% or less when held at melting point + 30°C for 30 minutes in a non-oxidizing atmosphere in thermogravimetric analysis (TG).

Citation Information

Patent Citations

  • Polyaryl ether nitrile resin and industrialized synthetic method thereof

    CN102766255A

  • Synthesizing method of high-molecular-weight polyarylene ether nitrile

    CN110305312A

  • Novel cyanoaryl ether polymer and its production

    JP1986057619A

  • Dehumidifying device

    JP1988062526A

  • Production of polycyanoaryl ether

    JP1988270733A